Comparative Study of Dexmedetomidine vs Esmolol for Attenuation of Stress Responses to Laryngoscopy and Endotracheal intubation. (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background: Endotracheal intubation is gold standard of general anaesthesia. But it has disadvantages of initiation of stress response to laryngoscopy and intubation. To alleviate it we have used Dexmedetomidine & Esmolol.Methods Group E - Inj. Esmolol (1.0 mg/kg) in 10 ml normal saline two minutes before induction Group D – Inj. Dexmedetomidine (1μg/kg) in 10 ml normal saline over 10 minutes prior to induction.Results and conclusion : both the drugs effectively supress stress response but Dexmedetomidine is better than Esmolol
Keywords: Dexmedetomidine; Esmolol; Stress response